Efforts to Improve Teachers' Ability to Develop Assessment Programs through In-House Training Activities - Taopik Taopik (Journal of Social Science, 2023)
School development aims to achieve 8 National Education Standards (SNP) Government Regulation (PP) RI No. 32 of 2013 concerning changes to PP No. 19 of 2005 concerning National Education Standards. The achievement of 8 SNPs, specifically for Assessment Standards, is carried out by conducting In House Training (IHT) activities. The purpose of this study is to improve the achievement of 8 (eight) National Education Standards, Provide excellent and optimal services to students and parents and the community. The methods used for initial data collection before IHT and after are: Document mining using the teacher data checklist method that collects education assessment programs before IHT, Interviews, Tests, Postes, Document mining using the teacher data checklist method that collects education assessment programs after IHT. The result was a significant difference from the pretest result of 46.67 and the posttest result of 72.29. Based on the existing results, it can be concluded that the increasing ability of teachers in compiling educational assessment programs, preliminary data before IHT was obtained 6 people did not compile educational assessment programs, 42 people compiled education assessment programs but were incomplete and no one compiled a complete education assessment program. After the implementation of IHT, data were obtained: there were no teachers who did not compile an educational assessment program, 2 people compiled an incomplete but then improved and 46 people compiled a complete education assessment program.